Konekcionizam u modeliranju prometnih informacijskih sustava
Connectionism represents a possible approach to the resolution of the issues of insufficiently described traffic systems. The system for keeping records on transport capacities of the fleet has been structured by a system of processing units. The output of an individual unit has been determined by the number of products of multiplication of the incidence of input attributes and the strength of their association links. The proposed model has been implemented for vehicles of the fleet described with eight groups (classes) of information. Verification of the application of the connectionism model within the scope of expedite monitoring (follow-up